Comparative Aspects of Electronic Government Service Maturity and “E-Diamond” Models - Tadas Limba (Social Technologies, 2013)
Nowadays electronic government starts dominating in all world countries. Some states are more experienced, while others have just started implementing it. Nevertheless, regardless of which models the country had reached, all of them should make the progress. It is important to try to overlook and analyze in essence the e-government services maturity and “E-Diamond” models at the public administration level, that are used in various countries. Having studied the peculiarities of stage models of electronic government services and having carried out their comparative analysis, the work shows the main similarities and differences of the models. Implementation of electronic government services in stage models is grounded on the complexity of service integration—a deeper integration of electronic government services is possible only having stepped through the lower integration stage. Swedish scientists A. Persson and G. Goldkuhl consider this policy of stage integration of services to be a disadvantage and they developed a contrapositional model “E-Diamond” which provides conditions to set free the stages and let them operate individually, not dependent on each other. Stages’ models have different requirements for self-identification in information systems. “ANAO,” “SAFAD,” “Hiller&Belanger” stages’ models require self-identification passing from the second to the third levels, while in stages’ models “Lee&Layne” and “Recreation of Public Sector Processes” requirements for self-identification appear in the second stages of providing electronic government services. Having carried out comparative analysis of all models of electronic government services six key features of the model are distinguished, such as possible levels of implementation, attributes of different levels, targeting the customer, targeting the inside processes, possibility to evaluate services, technological background. However, out of six features the main ones are considered to be the feature of targeting at the inside organizational processes of self-government and the feature of targeting at the customer. The implementation of the above mentioned features is identified in the models of “Stages” and “E-Diamond.” Both of them are quite equally targeted at restructuring inside processes and meeting the needs of customers. Assessing the models of “Stages” and “E-Diamond” according to this rather neutral targeting, they can be applied in economically developing as well as highly developed countries, thus can be considered to be universal. All in all, despite which model is used, there are lots of areas, where governments should improve their actions. They should look ahead, if they want to do their best at e-government policy.